KETAHANAN IKM DAN UMKM DAN STRATEGI PENGEMBANGAN USAHA TENUN GEDOGAN PRINGGASELA LOMBOK MELINTAS BENCANA GEMPA DAN PANDEMI COVID-19 - Mohamad Zaki Taufik (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2023)
A year after the Lombok earthquake, the economy of NTB Province contracted positively but in early 2020, the economy of NTB province again experienced negative growth of 4.52% due to the Covid-19 Pandemic. This condition requires resilience for IKM and UMKM to continue the productive businesses that have been initiated. This research aims to know the resilience of IKM and UMKM and strategies for developing Post-Disaster IKM and UMKM of the Pringgasela Lombok gedogan weaving business after the earthquake and Covid-19 pandemic. The description of the resilience of IKM and UMKM in crossing the 2018 Lombok Earthquake Disaster and the Covid-19 Pandemic analyzed by OODA Loops and strategies for developing Post-Disaster IKM and UMKM analyzed through Competitive Strategy Determination Analysis. IKM and UMKM of Pringgasela's gedogan weaving were able to survive the disaster through weavers' activities to take advantage of the free time to work on products to produce weaving stock even though disaster conditions were still ongoing. Good collaboration activities between weaving crafters, artshop owners, travel agents and tour guides in order to improve connections and the use of online media in the promotion and marketing of woven products provide opportunities for the sale of Pringgasela gedogan weaving stock. Market development strategies through the utilization of online media in product promotion and marketing became the strategy that had the highest attractiveness followed by type of cooperation strategy through increasing a sense of solidarity to build collective strength in the face of disaster. The type of product development strategy through increasing product diversification and variation of motifs became the order of priority strategies in the development of weaving businesses after the disaster.